Exciton valley dynamics in monolayer WSe2 probed by the two-color ultrafast Kerr rotation. Issue 4 (13th January 2017) - Yan, Tengfei; Ye, Jialiang; Qiao, Xiaofen; Tan, Pingheng; Zhang, Xinhui
Abstract : The exciton valley dynamics in monolayer WSe2 is investigated by the two-color pump–probe magneto-optical Kerr technique. Abstract : The newly developed two-dimensional layered materials provide a perfect platform for valley-spintronics exploration. To determine the prospect of utilizing the valley degree of freedom, it is of great importance to directly detect and understand the valley dynamics in these materials. Here, the exciton valley dynamics in monolayer WSe2 is investigated by the two-color pump–probe magneto-optical Kerr technique. By tuning the probe photon energy in resonance with the free excitons and trions, the valley relaxation time of different excitonic states in monolayer WSe2 is determined. Valley relaxation time of the free exciton in monolayer WSe2 is confirmed to be several picoseconds. A slow valley polarization relaxation process is observed to be associated with the trions, showing that the valley lifetime for trions is one order of magnitude longer than that of free excitons. This finding suggests that trion can be a good candidate for valleytronics applications.